’Target the Taste’ - A comprehensive review on different types of taste disorders - DR. S.SANDHYA; DR. S.RAGAVI (International Journal of Pharma and Bio Sciences, 2019)
Taste disorders, including ageusia, hypogeusia, dysgeusia and hypergeusia can have a substantial, negative impact on general health. Many of us take our sense of taste for granted, but a taste disorder can have a negative effect on quality of our life. Gustatory dysfunctions are implicated in loss of appetite, unintended weight loss, malnutrition, and reduced quality of life. Dentists are often the first to be presented with complaints about taste dysfunction (DYSGEUSIA). In recent years we have become much better in the assessment of ability to taste. This review provides a summary of the common causes of dysgeusia, problems associated with assessing taste function in a clinical setting and management options available to the dentist.